Wiedza studentów na temat odnawialnych źródeł energii = Knowledge of students about renewable energy sources - Mateusz Babula; Martyna Warchoł (Journal of Education, Health and Sport, 2016)
Babula Mateusz, Warchoł Martyna. Wiedza studentów na temat odnawialnych źródeł energii = Knowledge of students about renewable energy sources. Journal of Education, Health and Sport. 2016;6(8):135-144. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59905